Sequential two-stage autohydrolysis biorefinery for the production of bioethanol from fast-growing Paulownia biomass - Domínguez, Elena (2020)
Non-isothermal autohydrolysis, an environmentally friendly pretreatment, was employed for the production of second generation bioethanol from fast-growing Paulownia wood, comparing two biorefinery strategies: (i) one-stage autohydrolysis pretreatment, and (ii) sequential two-stage autohydrolysis pretreatment. The first strategy allowed to either recover high amounts of hemicellulosic-derived compounds in the liquid phase (at lower severities) or to achieve high enzymatic susceptibility of the cellulose in the solid phase (at higher severities). Solid phase from lower severities pretreatments (optimal for the recovery of hemicellulosic compounds) achieved glucan to glucose conversions of 38.672.2% in the enzymatic hydrolysis assays. In this context, conditions for the obtainment of a liquor enriched in hemicelluloses and a highly enzymatically susceptible solid are not compatible. Therefore, the employment of the second strategy (sequential pretreatments in two stages) allowed to recover up to 85% of initial xylan as xylooligosaccharides and xylose in autohydrolysis liquor from first stage of autohydrolysis (at severity, S01 = 4.08) and enhance the enzymatic susceptibility of the solid phase to a glucan to glucose conversion close to 100% with the second stage of autohydrolysis (S01 = 4.08, S02 = 3.76, with a global severity of S0G = 4.25). Fermentation experiments confirmed the advantages of the sequential two-stage autohydrolysis (with a glucan to ethanol conversion close to 100% and high volumetric productivity). Finally, an overall mass balance and energy analysis were carried out, reflecting a suitable fractionation of Paulownia wood that would accomplish an energy recovery of 97.5%.